2022
DOI: 10.1016/j.resp.2021.103805
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intrathoracic vagotomy on the cough reflex in the anesthetized cat

Abstract: Recurrent laryngeal afferent fibers are primarily responsible for cough in response to mechanical or chemical stimulation of the upper trachea and larynx in the guinea pig. Lower airway slowly adapting receptors have been proposed to have a permissive effect on the cough reflex. We hypothesized that vagotomy below the recurrent laryngeal nerve branch would depress mechanically or chemically induced cough. In anesthetized, bilaterally thoracotomized, artificially ventilated cats, thoracic vagotomy nearly elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…[49][50][51][52] The observation that UTC appears diminished in both these populations may support findings in animal studies where, irrespective of if cough is stimulated at the larynx or intrathoracic airway, lung-volume related and pulmonary vagal afferent feedback was associated with modulation of cough. 22 Our RR findings are consistent with previous reports in patients with pulmonary disease, 53,54 and further align with a scoping systematic review which suggested that elevated RR is a physiologic risk factor for aspiration. 55 In a previous investigation, Scherer et al 56 measured ventilatory regulation in LT recipients during carbon dioxide rebreathing, finding that LT recipients had significantly lower maximum tidal volume and RR compared to healthy controls.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…[49][50][51][52] The observation that UTC appears diminished in both these populations may support findings in animal studies where, irrespective of if cough is stimulated at the larynx or intrathoracic airway, lung-volume related and pulmonary vagal afferent feedback was associated with modulation of cough. 22 Our RR findings are consistent with previous reports in patients with pulmonary disease, 53,54 and further align with a scoping systematic review which suggested that elevated RR is a physiologic risk factor for aspiration. 55 In a previous investigation, Scherer et al 56 measured ventilatory regulation in LT recipients during carbon dioxide rebreathing, finding that LT recipients had significantly lower maximum tidal volume and RR compared to healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…This cohort of LT recipients who undergo denervation of the lower airway distal to anastomosis provides a unique contrast to published data in individuals undergoing total laryngectomy who lack laryngeal afferents 49–52 . The observation that UTC appears diminished in both these populations may support findings in animal studies where, irrespective of if cough is stimulated at the larynx or intrathoracic airway, lung‐volume related and pulmonary vagal afferent feedback was associated with modulation of cough 22 …”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Cough can be elicited by the activation of mechanically sensitive vagal afferent nerves projecting to the large airways (some specialised Aδ fibres, commonly named cough receptors) and lungs [mechanoreceptors, including rapidly adapting receptors (RARs) and slowly adapting receptors (SARs)] (15). In preclinical animal studies, the invasive intratracheal mechanical stimulation was found to induce the cough reflex in anaesthetised rabbits/cats/dogs (16)(17)(18)(19)(20). For humans in clinical practice, the common area where the mechanical stimulation has been applied are the large airways level and the chest (8,9).…”
Section: Mechanical Challenge Testsmentioning
confidence: 99%